Exploring job satisfaction amongst government social workers in East London - Sela, Michelle (Rhodes University, Faculty of Humanities, Department of Social Work, 2001)
During this research an attempt was made to gain an understanding of job satisfaction amongst government social workers. To achieve this, twenty social workers employed at the Department of Welfare in East London and Mdantsane were interviewed. South African literature on this topic is limited and it is believed that this study will present a valuable basis to pursue in further research. Literature that was consulted was found to be supportive of the theoretical notion that social work has long been recognised as being a stressful profession and that the nature of social work practice itself can be potentially stressful. The study found that there are many stressors and dissatisfactions which government social workers are currently experiencing. Some of the social workers have indicated a desire to leave the profession as a result of the dissatisfactions. The study findings suggest a need for combining oganisational with individual oriented initiatives to decrease the many stressors the social workers are experiencing. The thesis ends with recommendations of various strategies for addressing the concerns of the social workers in order to increase their job satisfaction
Keywords: Social workers -- Supervision of; Social workers -- Professional ethics; Social workers -- South Africa -- Eastern Cape -- Attitudes; Social service -- Vocational guidance